Is Life Insurance Crucial to Society and the Economy? Evidence from Asian Countries both before and after the Global Financial Crisis - Hassan, Fatin Aminah (Asian Development Policy Review, 2022)
Life insurance is not merely vital for the economic development of a country but also the health of an individual’s financial circumstances. This study examines the income elasticity of life insurance consumption and the impact of life insurance markets on economic growth in 22 Asian countries from 2001 to 2016. According to a panel data analysis of life insurance demand, it is inelastic in proportion to GDP per capita, implying that the product is a necessity for Asians. Furthermore, the results of a life insurance growth analysis conducted both before and after the 2007/2008 subprime crisis revealed that life insurance markets had a significant impact on economic growth. The findings showed the region’s life insurance industry was hit hard by the crisis and shed more than 10% of its market value relative to the economy. This work provides a valuable reference and recommendations for corporations and government sectors to strengthen these countries’ life insurance markets.